DASAR WAJIB MEMATUHI UNDANG-UNDANG PERKAWINAN (UUP): STUDI PEMIKIRAN MUHAMMAD ‘ABDUH - Nasution, Khoiruddin (Indonesian Association of Islamic Family Law Lecturers, 2019)
One reason why the Marriage Law (UUP) is not obeyed is related to the status of compliance. According to the majority of Muslims, the status of obeying the contents of the UUP is related to and is a matter of the State, not related to the legality of religion, not related to the validity of marriage. Instead Muhammad 'Abduh is a thinker who believes that obeying the UUP is part of an obedient obligation to the government (uli al-amr), the same status as being obliged to obey Allah and His messengers, as required in al-Nisa' (4): 59 and 83. Thus, obeying the UUP is part of implementing compliance with the government. So obeying UUP is an obligation for every Muslim. Likewise, the UUP as a decision of people's representatives is an expression of the agreement of all the people. The people are represented by people who are elected by the people (people's representatives), because to gather all the people, at present, is impossible. So the decision of the people's representatives is positioned as the decision of all the people. The decision of the people's representatives for now becomes ijmâ ‘, the third source of Islamic law after the Qur'an and the Sunnah of the Prophet Muhammad SAW. The final basis stipulates the obligation to obey the Marriage Law, compared to fiqh, fatwa, interpretation, and jurisprudence, as a product of Islamic legal thinking, the UUP occupies the most authoritative and comprehensive position, because the UUP is the result of the minds of many scholars and expertise. This paper tries to explain the concept of ‘Abduh.